Disparity in Parliamentary Power in the Formation of Laws in Indonesia: Considering Proportional Bicameralism - Mukhlis, Muhammad Mutawalli; Arowosaiye, Yusuf Ibrahim; Masum, Ahmad; Paidi, Zulhilmi Bin; Maskun (NAJAHA, 2025)
This research aims to investigate the issues encountered by parliamentary institutions in Indonesia, focusing specifically on the disproportionate power of the first chamber the (Dewan Perwakilan Rakyat / DPR) People’s Representative Council, relative to the second chamber, the (Dewan Perwakilan Daerah / DPD) Regional Representative Council throughout the legislative process. This research presents normative-conceptual proposals for a reconstruction formula aimed at equilibrating the legislative functions of the two chambers, in alignment with the principles of balanced or robust bicameralism. This study utilises a doctrinal legal research framework, involving the analysis of primary and secondary legal sources in the literature. This study incorporates constitutional, theoretical, and statutory/normative techniques. This study applies a general qualitative descriptive analysis technique, focusing on interpreting legal texts and normative content in a structured manner to identify patterns, meanings, and implications in the legislative relationship between DPR and DPD. The research findings reveal that the legislative authority of the two chambers (DPD & DPR) in legislation making, as delineated in the 1945 Constitution of the Republic of Indonesia and statutory rules, remains disproportionate. This results from the DPD's limited authority to propose draft legislation and discuss proposals without final approval. The DPD continues to be acknowledged as a co-legislator or supplementary power in the legislative process, unlike the unrestricted authority of the DPR. Therefore, the relationship between the two chambers as representative entities must be redefined based on robust or equitable bicameralism. To execute rebuilding plans, it is essential to amend several parts of the Constitution and revise other legislative rules. The two chambers are expected to collaborate and meet the ambitions of both national and local governments to produce high-quality legal documents; however, this study is limited in scope to normative and doctrinal analysis, and further empirical research is needed to assess practical implementation.